Association between the atherogenic index of plasma and the occurrence of acute kidney injury in critically ill patients with sepsis: A retrospective study - Bing Wu; Pengli Wei; Jiaxiang Deng; Yuanyuan Rui (PLoS ONE, 2025)
Background The atherogenic index of plasma (AIP) is a recognized marker of atherosclerosis and cardiovascular disease (CVD). However, the association between AIP and the risk of acute kidney injury (AKI) in critically ill patients with sepsis has not yet been investigated. Methods The data used in this study were derived from the Medical Information Mart for Intensive Care (MIMIC-IV) database. The clinical outcome was the occurrence of AKI. Logistic regression was used to assess the association between AIP and the risk of AKI in sepsis patients. Restricted cubic spline (RCS) analysis was applied to explore potential non-linear relationships. Threshold analysis confirmed a turning point at this value. Subgroup analyses evaluated the consistency of the association across different strata. Mediation analysis was performed to explore potential intermediate variables. Results Among 1,874 sepsis patients, higher AIP levels were associated with increased AKI incidence. Logistic regression showed a significant association between AIP and AKI in unadjusted and partially adjusted models, but the association was no longer significant after full adjustment. RCS analysis revealed a nonlinear relationship with a peak AKI risk at AIP = 1.333. Threshold analysis confirmed a turning point at this value. Subgroup analyses showed consistent associations, while nonlinear effects were more evident in specific groups. Mediation analysis suggested that SOFA score, creatinine, WBC count, and respiratory rate partially mediated the AIP-AKI relationship. Conclusion AIP was nonlinearly associated with AKI in sepsis, with a clear threshold effect. This relationship was partially mediated by SOFA score, creatinine, WBC, and respiratory rate. AIP may serve as a useful marker for AKI risk assessment.